Consepts of glory and honour in Ukrainian wedding’s conceptual field - Заверющенко, Ольга Леонідівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In this article are investigated consepts of glory and honour in Ukrainian wedding’s conceptual field which include concepts connected with wedding realities, participants of wedding action, moral categories and so on. The base of concepts consolidation are established in the article in common subgroup "Moral principles of behavior". On material of folklore records, dialectal dictionaries and dictionaries of modern Ukrainian, works of fiction the dynamics of development of the adopted concepts is analysed. Etymological analysis of lexemes glory and honour is conducted and their meanings are cleared up. Connection of concept glory is traced with other wedding concepts such as memory, will. Consept honour is connected with other moral principals as shame, honesty, chastity. Great attention is paid to filling of the mentioned concepts by the morals which are intended for unmarried young people. These concepts are recommended by Ukrainian folk morals. A role and place of these concepts are defined in the Ukrainian wedding conceptual field for forming of the idea of pre-wedding normative young people’s behavior, society moral principles, it’s reaction to violation of Ukrainian folk morals.